Hydrographic Surveys in Disputed Areas - Hansen, Lars; Kowalski, Andrzej (The International Hydrographic Review, 2014)
In 2011, during the 16th Baltic Sea Hydrographic Commission (BSHC) Conference in Norrköping (Sweden), Poland submitted for discussion and consideration the problem of surveying tasks in sea areas claimed by more than one coastal state. An example of this problem still exists between the Danish Bornholm Island and the Polish Coast in the Baltic Sea (see Figure 1). The Polish delegation presented the opinion that procedures for hydrographic surveys and general hydrographic tasks, done in disputed areas, should be worked out. In spite of the fact that Hydrographic Services have not been established to resolve disputes of any kind, which are in the domain of diplomacy, the Services (both Polish and Danish in this respect) remain responsible for surveying such areas. However, how can this responsibility be fulfilled when there are no procedures explicitly regulating particular hydrographic activities in these areas? If such circumstances sustain, sooner rather than later, the safety of navigation will suffer. The mentioned Zone is a result of the unsettled dispute between Poland and Denmark over limits of Exclusive Economic Zones (EEZ).